2017
DOI: 10.1159/000464347
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death in End Stage Renal Disease: Comparing Hemodialysis versus Peritoneal Dialysis

Abstract: Background/Aims: This study aimed to evaluate total and sudden death (SD) in a cohort of dialysis patients, comparing hemodialysis (HD) vs. peritoneal dialysis (PD). Methods: This is a multicenter retrospective cohort study. Results: Deaths were 626 out of 1,823 in HD and 62 of 249 in PD patients. HD patients had a greater number of comorbidities (p < 0.05). PD patients had a lower risk of death than HD patients (p < 0.001); however, the advantage decreased with time (p < 0.001). Mortality predictors were left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 43 publications
(55 reference statements)
0
21
1
1
Order By: Relevance
“…According to another previous study, increased LVEDD was an independent predictor of all-cause mortality [27]. In addition, Genovesi et al [28] reported that LVEF ≤35% in dialysis patients was a predictor for allcause and sudden death mortality. Meanwhile, compared with conventional HD, frequent nocturnal HD improved LV mass [8,29] and LVEF [12], and reduced blood pressure [11].…”
Section: Discussionmentioning
confidence: 94%
“…According to another previous study, increased LVEDD was an independent predictor of all-cause mortality [27]. In addition, Genovesi et al [28] reported that LVEF ≤35% in dialysis patients was a predictor for allcause and sudden death mortality. Meanwhile, compared with conventional HD, frequent nocturnal HD improved LV mass [8,29] and LVEF [12], and reduced blood pressure [11].…”
Section: Discussionmentioning
confidence: 94%
“…A total of 33 studies underwent a full‐length article review, and 18 of them were excluded as they did not include controls or did not report the outcome of interest. Therefore, a total of 15 studies met our inclusion criteria and were included in the meta‐analysis. Figure outlines our search methodology and selection process.…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear whether the choice of dialysis modality affects the risk of stroke . Each renal replacement modality causes physiological changes that may affect the risk of stroke in a different way .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that LV masses were associated with all-cause mortality and cardiovascular mortality for ESKD patients [26]. In addition, Genovesi et al [27] reported that one predictor of all-cause mortality and sudden death mortality was LVEF ≤35% for dialysis patients. However, in a multicenter, randomized, controlled trial, treatment of patients with hypertension for 18 months promoted favorable effects for LV remodeling.…”
Section: Discussionmentioning
confidence: 99%